Enhancing the Interfacial Property Between UHMWPE Fibers and Epoxy Through Polydopamine and SiO2 Surface Modification - Nengjun Ben; Sulun Jiang; Liping Zhao; Jiale Gong; Lu Shen; Kui Wang; Chenyang Tang (ChemistryOpen)
Abstract Here, a combination of dopamine self‐polymerization and epoxy modified SiO2 (M‐SiO2) grafting was proposed, with the purpose of increasing interfacial adhesion of UHMWPE fiber. Inspired by mussel adhesion, polydopamine (PDA) was deposited onto the surface of UHMWPE fiber to form a thin layer with amino and hydroxyl groups. M‐SiO2 nanoparticles were then adhered to fiber surface via chemical reactions by a “two‐step” or “one‐step” technology. In the “two‐step” technique, the M‐SiO2 nanoparticles were adhered to the surface of PDA modified UHMWPE fiber via reactions between epoxy and amino groups. In the “one‐step” method, M‐SiO2 and dopamine were added into the UHMWPE/Tris solution at the same time. Surface morphology and thermal properties of various UHMWPE fibers were tested by SEM and TGA, respectively. Surface wettability of different UHMWPE fibers were evaluated by dynamic contact angle. The results proved that PDA and M‐SiO2 were successfully adhered to the surface of UHMWPE fibers. The mechanical property of modified UHMWPE/Epoxy composites was investigated, and 43.7 % improvement was obtained, compared with unmodified UHMWPE/Epoxy composite. Additionally, micro‐bond test revealed that the interfacial property (IFSS value) of modified UHMWPE fiber via the “one‐step” method was 6.08 MPa, significantly higher than that of unmodified UHMWPE fiber (2.47 MPa).